Input varieties and growth: A micro-to-macro analysis - David Baqaee; Ariel T. Burstein; Cédric Duprez; Emmanuel Farhi (National Bank of Belgium, 2023)
We investigate the effects of input variety creation and destruction on both micro- and macroeconomic outcomes using detailed data from Belgium. Our microeconomic analysis establishes that the elasticity of downstream firms' marginal cost to supplier separation captures the area under the input demand curve, and this elasticity can be utilized to calibrate love-of-variety and Schumpeterian models. Empirically, we estimate that marginal costs rise by 0.6% for every 1% of suppliers lost. Our macroeconomic analysis develops a growth-accounting framework that captures the role of supply chain churn for aggregate growth. Using firm-level production network data and estimated microeconomic elasticities, we show that supplier churn can plausibly account for a large portion of the trend component of growth in aggregate productivity. Our findings highlight the crucial role of input entry and exit in driving economic growth.
Keywords: D21; D22; E10; 330; growth; churn; exit; entry